2015
DOI: 10.1021/acs.jmedchem.5b00881
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Synthesis and Biological Activities of 20S,24S/R-Dihydroxyvitamin D3 Epimers and Their 1α-Hydroxyl Derivatives

Abstract: Bioactive vitamin D3 metabolites 20S,24S-dihydroxyvitamin D3 [20S,24S(OH)2D3] and 20S,24R-dihydroxyvitamin D3 [20S,24R(OH)2D3] were chemically synthesized and confirmed to be identical to their enzymatically generated counterparts. The absolute configurations at C24 and its influence on the kinetics of 1α-hydroxylation by CYP27B1 were determined. Their corresponding 1α-hydroxyl derivatives were subsequently produced. Biological comparisons of these products showed different properties with respect to vitamin D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 30 publications
(98 reference statements)
2
43
0
Order By: Relevance
“…While originally produced by enzymatic synthesis in amounts enabling identification, chemical routes of synthesis for 20(OH)D3, 20,23(OH) 2 D3 and 20,24(OH) 2 D3 have now been established [64, 65, 6769] which also confirmed that the enzymatically produced 20(OH)D3 is the 20 S enantiomer [67]…”
Section: New Pathways Of Vitamin D Activationmentioning
confidence: 99%
See 4 more Smart Citations
“…While originally produced by enzymatic synthesis in amounts enabling identification, chemical routes of synthesis for 20(OH)D3, 20,23(OH) 2 D3 and 20,24(OH) 2 D3 have now been established [64, 65, 6769] which also confirmed that the enzymatically produced 20(OH)D3 is the 20 S enantiomer [67]…”
Section: New Pathways Of Vitamin D Activationmentioning
confidence: 99%
“…20(OH)D3 and its hydroxymetabolites exert prodifferentiation, antiproliferative, and antiinflammatory activities on skin cells, comparable or better than that of 1,25(OH) 2 D3 [53, 64, 65, 67, 70, 8392]. 20(OH)D3 shows antifibrotic properties both in vitro [8789] and in an in vivo mouse model of bleomycin induced scleroderma [89].…”
Section: Biological Activity Of Cyp11a1-derived Vitamin D Hydroxydmentioning
confidence: 99%
See 3 more Smart Citations